Preliminary Research on Reinforcement Schemes for New Composite Dam Structure of Mortar Masonry-Concrete ——A Case Study of Chi'ao Reservoir in Shenzhen City - CHEN Yu; YANG Xiuchun; DU Jiakai; XU Menghua (Renmin Zhujiang)
The main masonry dam of Chi'ao Reservoir in Shenzhen faces insufficient overall anti-sliding stability safety margin and leakage of the left dam abutment.In view of these problems,this paper proposed a new reinforcement technology for a composite dam of mortar masonry-concrete based on engineering characteristics and designed two different reinforcement schemes for the composite dam of mortar masonry-concrete,such as anti-seepage reinforcement before the dam and the thickening reinforcement after the dam.Furthermore,the paper evaluated the anti-sliding stability and anti-seepage effect of the two schemes.The results show that both schemes meet the relevant specification requirements.